Leadership of the School Principal in Increasing Teacher Competency in State Elementary School 09 Pemulutan - Dellyana Dellyana; Yasir Arafat; Muhammad Fahmi (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Education in Indonesia faces various challenges to meet the demands of a growing society. One of the important aspects in improving the quality of education is teacher competence. The leadership of the principal plays a significant role in encouraging the improvement of teacher competence, which in turn will have an impact on the quality of learning in schools. This study aims to describe how the principal's leadership in improving teacher competence at State Elementary School 09 Pemouthan, as well as the factors that support and hinder the process and how to overcome these obstacles. This research uses a qualitative descriptive approach through observation, interviews and documentation. The results of the study show that the principal of State Elementary School 09 Pemouthan in improving teacher competence has implemented various leadership strategies, including by acting as an educator, manager, administrator, supervisor, leader, innovator and motivator to improve teacher competence. The supporting factors encountered include the provision of resources, the use of technology in learning, and creating a positive work environment. Meanwhile, inhibiting factors include budget limitations, resources, time, lack of self-motivation and resistance to change. To overcome this, the principal encourages teachers to optimize the use of technology and the internet to access online training materials, build a positive learning culture by forming a learning community and involving driving teachers as resource persons, as well as providing rewards as competency support.